Hymenoptera venom allergy in outdoor workers: Occupational exposure, clinical features and effects of allergen immunotherapy - Alessandra Toletone; Susanna Voltolini; Giovanni Passalacqua; Guglielmo Dini; Donatella Bignardi; Paola Minale; Emanuela Massa; Alessio Signori; Costantino Troise; Paolo Durando (Taylor & Francis Group, 2017)
Objectives. To describe (i) the clinical characteristics of workers, exposed to hymenoptera stings, with an ascertained diagnosis of Hymenoptera Venom Allergy (HVA), (ii) the specific role of occupational exposure, (iii) the effect of Venom Immunotherapy (VIT) in reducing the severity of allergic episodes in workers exposed to repeated stings of hymenoptera, and (iv) the management of the occupational consequences caused by allergic reactions due to hymenoptera stings. Methods. Between 2000 and 2013 an observational study, including patients referred to the regional reference hospital of Liguria, Italy, with an ascertained diagnosis of HVA and treated with VIT, was performed. A structured questionnaire was administered to all patients to investigate the occupational features of allergic reactions. These were graded according to standard systems in patients at the first episode, and after re-stings, during VIT. Results. One-hundred and 8four out of the 202 patients referred had a complete data set. In 32 (17.4%) patients, the allergic reaction occurred during work activities performed outdoor. Of these, 31.2% previously stung by hymenoptera at work, and receiving VIT, were re-stung during occupational activity. The grades of reaction developed under VIT treatment resulted clinically less severe than of those occurred at the first sting (p-value = 0.031). Conclusion. Our findings confirmed the clinical relevance of HVA, and described its occupational features in outdoor workers with sensitization, stressing the importance of an early identification and proper management of the professional categories recognized at high risk of hymenoptera stings. The Occupational Physician should be supported by other specialists to recommend appropriate diagnostic procedures and the prescription of VIT, which resulted an effective treatment for the prevention of episodes of severe reactions in workers with a proven HVA.